EL PAPEL DE LA FAMILIA EN EL APRENDIZAJE COMPARTIDO DE LA REGULACIÓN EMOCIONAL COMO BIENESTAR SUBJETIVO - García Cruz, Rubén; Andrade, Norma Angélica Ortega; Guerrero, Ana María Rivera (European Scientific Journal, ESJ, 2013)
Learning emotional regulation is a process that involves the recognition, use, understanding and management of own and others emotional states from our historical and cultural experiences in their interaction with others in the world around us and that is justified from the diversity of social problems . The family is the primary system of links or attachments for learning emotional regulation. Authors such as De Castro (1996); Gligo (1996) and Mc Lanhan (1985) among others, recognize the powerful influence of the family in the education of children, affirm the role of parents in the education process. Bisquerra (2003) argues how learning emotional competence is regarded as a basic skill for life, need to be developed through emotional education as a process that seeks to respond to a set of social needs that are not adequately addressed in formal education and that their origins are in the family, on the other hand. Jadue (2003) recognizes that social and emotional competence is the ability to understand, manage and express the emotional aspects of our own lives so that we are able to handle everyday tasks such as learning, interpersonal and social relationships, solving everyday problems and adapting to the complex demands of growth and development. Includes various aspects of both understanding and emotional expression as handling internal emotional experience and expressive behavior. This presents a theoretical reflection of sociocultural factors of the role of family in shared learning emotional regulation as subjective well-being